2015
DOI: 10.1111/1749-4877.12095
|View full text |Cite
|
Sign up to set email alerts
|

Sharks senses and shark repellents

Abstract: Despite over 70 years of research on shark repellents, few practical and reliable solutions to prevent shark attacks on humans or reduce shark bycatch and depredation in commercial fisheries have been developed. In large part, this deficiency stems from a lack of fundamental knowledge of the sensory cues that drive predatory behavior in sharks. However, the widespread use of shark repellents is also hampered by the physical constraints and technical or logistical difficulties of deploying substances or devices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 202 publications
(262 reference statements)
0
46
0
1
Order By: Relevance
“…While these measures aim to reduce the probability of sharks and humans encountering each other, other measures aim to repel sharks directly from approaching people in the water. These deterrents have been developed to elicit a response by impacting one or more of the shark’s senses, including vision, smell, and electro-reception (see Hart & Collin, 2015). For example, various aposematic colour configurations (i.e., use of colours as anti-predator tactics) have been alleged to repel sharks.…”
Section: Introductionmentioning
confidence: 99%
“…While these measures aim to reduce the probability of sharks and humans encountering each other, other measures aim to repel sharks directly from approaching people in the water. These deterrents have been developed to elicit a response by impacting one or more of the shark’s senses, including vision, smell, and electro-reception (see Hart & Collin, 2015). For example, various aposematic colour configurations (i.e., use of colours as anti-predator tactics) have been alleged to repel sharks.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of bubble curtains as shark deterrents found that after initial success, sharks eventually breached the curtain that was protecting a bag of burley (Hart and Collin, 2015). Sporadic pulses of large bubbles in conjunction with the continuous curtain of small bubbles are considered to be more effective at protecting the bait (Hart and Kempster personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…Bubble curtains have also been applied for fish herding in fishing and aquaculture, as a means of guiding fish in set-net fishing operations and retaining fish in enclosures (Stewart, 1982;Arimoto et al, 1993). Perhaps the most common application of bubble curtains, however, has been as a barrier to guide and deter the movement of aquatic species (Sager et al, 1987;Dawson et al, 2006;Zielinski et al, 2014;Hart and Collin, 2015). As deterrents, bubbles have been trialed and applied to prevent fish entering hydroelectric power stations (Linnansaari et al, 2015), restrict the movement of invasive species (Dawson et al, 2006;Zielinski et al, 2014) and as shark deterrents (Hart and Collin, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations